Reading For Writing: Exploring English Language Education Study Program Students’ In Improving Their Writing Skills - Pilongo, Jolanda Hulda Debora; Hatibie, Yunita; Gobel, Megi Sepriyanti (Research Review: Jurnal Ilmiah Multidisiplin, 2024)
This study aims to investigate how students in the English Language Education Study Program (ELESP) adopt their reading activities to stimulate improvement in writing English texts. This qualitative descriptive study focuses on participants from the Class of 2020. Data collection methods include pre-interviews, interviews, and analysis of students' writing samples. The data is subsequently analyzed using a qualitative descriptive approach. The results indicate that students' experiences significantly influence their writing skills. A lack of experience often results in lower motivation to write, which in turn leads to poorer writing performance and lower scores. Although students recognize the importance of reading for enhancing writing skills, their reading abilities alone do not necessarily translate into improved writing proficiency. The findings suggest that while engaging in reading activities can help students overcome some writing difficulties, it does not have a substantial impact on overall writing improvement. This underscores the need for more comprehensive approaches that integrate reading with other skill-enhancing activities to better support students' writing development. Further research could explore additional factors that contribute to writing proficiency and develop strategies to more effectively bridge the gap between reading and writing skills.